ANALISIS PENERAPAN PRINSIP BIOETIK PADA PENGELOLAAN LIMBAH B3 DILABORATORIUM KESEHATAN DAERAH KOTA BEKAS - NAUFAL MAHENDRA; ELSHA NURISA SIDABUTAR; Nurbaity Situmorang; Khairiza Lubis (Universitas Cokroaminoto Palopo, 2026)
The management of hazardous and toxic waste (B3) in health laboratories remains a challenge, particularly inensuring regulatory compliance while consistently applying bioethical principles. This issue is important becauseimproper waste management can negatively impact the environment and public health. Therefore, this study aimsto analyze the B3 waste management system, its compliance with regulations, and the implementation of bioethicalprinciples at the Regional Health Laboratory (Labkesda) of Bekasi City. This study employed a descriptivequalitative method with a case study approach. Data were collected through interviews, observations, anddocumentation involving two informants directly engaged in waste management. In addition, the implementationof bioethics was assessed using a Likert scale with ten indicators. The results show that B3 waste management hasbeen carried out in a structured manner, including identification, containment, transportation, temporary storage,and processing by licensed third parties, thus complying with applicable regulations. Furthermore, theimplementation of bioethical principles achieved an average score of 4.8 out of 5, indicating a very good category.However, an obstacle was identified in the form of delays in waste collection by third parties. In conclusion,Labkesda Bekasi City has been able to manage B3 waste effectively and sustainably, although improvements inexternal coordination are still needed